2016
DOI: 10.1093/ecco-jcc/jjw071
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Ulcerative Colitis is Related to Severe Inflammation and a High Count of Cytomegalovirus-positive Cells in Biopsy Is a Risk Factor for Colectomy

Abstract: Five or more CMV IHC-positive cells per biopsy section were indicative of a greater colectomy risk. CMV infection was related to more severe inflammation. Blood CMV PCR is a useful tool in UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 29 publications
0
34
0
2
Order By: Relevance
“…Another 22 articles were further excluded by reading the full text. Ultimately, 20 [9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were eligible for data extraction and meta-analysis. The searching process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Another 22 articles were further excluded by reading the full text. Ultimately, 20 [9,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] articles were eligible for data extraction and meta-analysis. The searching process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…Chen HP detected CMV by PCR in CRC tissues (42.3%) higher than in normal colorectal specimen (5.6%) [30]. Among 95 ulcerative colitis samples which were analyzed, 33 tissues were indicated the presence of CMV and 62 specimen were CMV negative [31]. Varicella-zoster virus is classified as one of the members of herps viridea that able to hide in nerve cells and resume activity in times of stress [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the high-density group, antiviral treatment significantly reduced the surgical rate. Regarding colectomy, Zagórowicz et al [37] reported that the group with numerous HCMV-infected cells in their intestinal tissue showed a significant decrease in colectomy rate with antiviral treatment. Kim et al [38] conducted a prospective study of 72 UC patients who were moderately or severely treated with steroids.…”
Section: Efficacy Of the Antiviral Treatmentmentioning
confidence: 99%